Career counseling by using self control technique to assist student career decision-making - Murni Pratiwi Putri (Ikatan Bimbingan dan Konseling Sekolah)
Adolescence is a time of increasing issues in decision-making about the future, friends, further education, university, major, job field, etc. Yet often students still find it difficult in making decisions about their future including careers. This literacy study aims to describe an idea of career counseling by using self-control techniques for student career decision-making. When students are faced with difficult career path choices, self-control plays an important role in decision-making. With the self-control, they make decisions by thinking and considering the long-term consequences of the problems they face, indeed with the strengthening of career counseling that is carried out. Various studies show that the things that greatly affect the decision-making of students is self-control. Students’ self-control is crucial to their success in decision-making.